Effects of water flow rate and surface cover plant density on the growth of duckweed (Lemna minor L.) - Hutabarat, Renata Caprina Samantha Mahadewi; Indradewa, Didik (Jurnal Ilmu Pertanian, 2020)
Globally, agriculture sector is facing unprecedented challenges in producing fertilizers and increasing the amount of fertilizer production without having negative impact on the environment. Thus, the organic fertilizers are needed to be produced as they do not give any damages to the environment. Duckweed plant has a lot of potentials that can be used in the agriculture sector. This plant can breed in approximately 16-48 hours by splitting. The water needs and its breeding speed ability are the basis for conducting this research. The research objective was to determine the effect of water flow rate and surface cover plant density on the growth and yield of duckweed plants. This research was conducted in November–December 2018 in Cangkringan District, Sleman, Special Region of Yogyakarta, Indonesia. The experiment was arranged in a split plot design. The main plot was irrigation water flow rate, consisting of two levels, namely large water flow rate (0.336 L.second-1) and small water flow rate (0.085 L.second-1). The subplot was the density of the duckweed plant surface cover, consisting of 10%, 20%, 40% and 60%. The results of this study indicated there was no effect of water flow rate on the plant growth, yield, and yield quality of duckweed plants. The C/N ratio of the duckweed plants fulfilled the requirement to be used as green manure.